Multiple Models Used to Deconstruct the Characteristics of Atmospheric Particles in Arid Region of Northwest China - Liu, Chao; Zhang, Tianhao; Lu, Bingqing; Zheng, Guozhong; Liu, Xiaoyan; Gao, Ying; Chen, Ying; Li, Xiang (Frontiers in Environmental Science, 2022)
Northwest China has a desert, arid and semi-arid climate that makes outdoor air sampling challenging. The region is also affected by intense dust storms. Monitoring challenges from the harsh climate have limited supplies of the data needed to inform appropriate regulatory actions to address air pollution in the region. Here we combine a comprehensive set of state-of-the-art offline analytical approaches and multiple models to deconstruct the chemical nature and sources of particulate matter at arid city in northwestern China. We collected 972 samples in Jiuquan during the period March 2019 through January 2020. The annual levels of PM10 (73.7 μg/m3) exceeded the Chinese Ambient Air Quality Standard (CAAQS) Grade II of 70 μg/m3. The percentages of the sum of sulfate, nitrate and ammonium, inorganic elements, organic carbon and elemental carbon in PM10 mass ranged 6.8–15.8%, 9.9–12.2%, 9.0–27.7%, and 1.5–4.7%, respectively. Analyses of sources indicated that soil dust was a major contributor to PM10 levels in Jiuquan city accounting for 24.8–30.5%. Fugitive dust and coal combustion were the second and third largest contributors to PM10, respectively. Our results suggest that natural emissions can make air quality regulation futile. In this comprehensive particulate pollution analysis, we present the view that the sizeable regional particulate sources warrant national and regional mitigation strategies to ensure compliance with air quality requirements.